2017
DOI: 10.15406/jmen.2017.05.00175
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Importance of the Association between Componotus Consobrinus and Potential Bacterial Pathogens in Human Dwellings

Abstract: Camponotus consobrinus, the banded sugar ant is so called because of its liking for sweet food. This study was carried out to determine the association between Camponotus consobrinus and potential bacterial pathogens in human dwellings and their public health importance. The ants were purposively collected from four locations; kitchens, bed rooms of various homes, shops and bakeries. Out of the 250 Camponotus consobrinus caught for the study, 90(36.0%) were caught in the kitchen, 75(30.0%) in the bed rooms 40(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other studies similarly identified fecal coliforms such as Enterobacter , Escherichia and Klebsiella spp., as well as pathogenic bacteria S. aureus on ants [32],[33]. Ogba et al [15] isolated a total of 205 species from Banded sugar ants ( Camponotus consobrinus ) and determined E. coli (fecal indicator bacteria; 30%) to be the most common isolate, followed by Morganella morganii (histamine-forming bacteria, 18%), Serratia marcescens (opportunistic pathogen, 4%) and Citrobacter freundii (coliform, 4%). Rodovalho et al [18] also isolated gram-negative bacilli at a carriage rate of 16.7% from ants ( Tapinoma melanocephalum and Camponotus vittatus ) and concluded that these insects may be responsible for carrying as well as distributing gram-negative bacilli in the hospital environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies similarly identified fecal coliforms such as Enterobacter , Escherichia and Klebsiella spp., as well as pathogenic bacteria S. aureus on ants [32],[33]. Ogba et al [15] isolated a total of 205 species from Banded sugar ants ( Camponotus consobrinus ) and determined E. coli (fecal indicator bacteria; 30%) to be the most common isolate, followed by Morganella morganii (histamine-forming bacteria, 18%), Serratia marcescens (opportunistic pathogen, 4%) and Citrobacter freundii (coliform, 4%). Rodovalho et al [18] also isolated gram-negative bacilli at a carriage rate of 16.7% from ants ( Tapinoma melanocephalum and Camponotus vittatus ) and concluded that these insects may be responsible for carrying as well as distributing gram-negative bacilli in the hospital environment.…”
Section: Resultsmentioning
confidence: 99%
“…Microbiological tests were carried out in order to identify any pathogenic microorganisms found on ants commonly present in domestic kitchens. The method of capturing and microbiologically analyzing ants was adapted from Maximo et al [14] and Ogba et al [15] respectively. Briefly, 50-ml centrifuge tubes, each containing 10 g of sugar, were heat-sterilized to act as baits.…”
Section: Methodsmentioning
confidence: 99%
“…Ants of the genus Camponotus occur in environments with structural flaws due to poor conservation of buildings. In the interior of buildings, ants of this genus are attracted to places with foods (Baccaro et al 2015, Ogba et al 2017, such as kitchens, canteens and places with the presence of residues. They can act as carriers of microorganisms such as Enterococcus sp., Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 99%